DYNAMIC BEHAVIOR OF TWO-SPAN CONTINUOUS CONCRETE BRIDGES UNDER MOVING OF HIGH-SPEED TRAINS - Marinichenko, O. H. (Science and Transport Progress, 2017)
Purpose. The scientific work provides a comparison of the results of the movement of a high-speed passenger train across the bridge, obtained as a result of finite element modeling in the SAP2000 software package, and real tests of a double-span concrete railway bridge. Analysis of the rigid characteristics of flying structures. Methodology.The numerical method presented in this study shows valid results concerning the dynamic analysis of the behavior of bridges in conditions of high-speed train traffic. The factors influencing the dynamic behavior of bridges under moving loads, the influence of design parameters and rolling stock, as well as the interaction of the train and spans are determined. The system was used in the form of moving concentrated forces simulating the axes of the train. Findings. Maximum movements and accelerations were obtained as a result of the dynamic calculation for different speeds of the train and compared with practical tests. The correctness of the model of a span structure with regard to continuous ferroconcrete spans was verified. Originality. Within the framework of the work, the latest test results were used, including those with speeds calculated on the prospect of rail passenger traffic. For these tests, a model of a span structure was developed. Practical value. The results of the research can be used to plan the introduction of high-speed train traffic on existing and planned flying structures of reinforced concrete bridges. An approach to the design of span structures that will be effective when passing high-speed passenger trains is implemented.